Tel Azekah 113 years after: preliminary evaluation of the renewed excavations at the site - Lipshits, ʿOded; Gadot, Yuval; Oeming, Manfred (Near Eastern archaeology, 2012)
Tel Azekah is located on a prominent ridge in the heart of the Judean Lowlands, Israel. Biblical as well as extrabiblical sources mention Azekah as one of the Judahite border towns of the late eighth to early sixth century b.c.e. that faced the territory of the Philistines. The site was first excavated in 1898-1899 by the British archaeologist F. J. Bliss, assisted by R. A. S. Macalister, on behalf of the Palestine Exploration Fund. In the summer of 2012, 113 years later, excavations were renewed by the Tel-Aviv and Heidelberg Lautenschlüger Azekah expedition. This article presents the research goals of the team, followed by a preliminary report of the finds from the first season, including substantial remains from the Late Bronze Age. Other remains found date to the Early Bronze Age, Middle Bronze Age, Iron Age II, and Hellenistic and Late Roman periods.